Analisis Konsep Keadilan dalam Hukum Islam dan Implikasi terhadap Moderasi Beragama - Anfasa, Farid; Ja'far, A. Khumedi (Moderasi : Journal of Islamic Studies, 2025)
This study examines the Islamic concept of justice and its implications for strengthening religious moderation in increasingly plural and globalized societies. Justice, as a foundational principle in Islamic legal and ethical thought, encompasses theological, juridical, social, and moral dimensions that emphasize fairness, equality, human dignity, and the protection of rights without discrimination. Using a qualitative design grounded in a normative–theological approach and an extensive review of primary Islamic sources—including the Qur’an, hadith, and classical as well as contemporary juristic scholarship—this research analyzes the multidimensional structure of justice within Islamic law. The findings reveal six major conceptual domains: divine command justice, impartial justice beyond social status or group identity, judicial justice, socio-economic justice, interreligious justice, and justice within family and gender relations. These dimensions demonstrate a strong doctrinal alignment with the core principles of religious moderation (wasathiyyah), particularly balance, tolerance, equality, and openness. The study argues that embedding justice as the ethical foundation of religious moderation offers a substantive framework for countering extremism, reducing intolerance, and fostering inclusive coexistence. This research contributes to contemporary Islamic discourse by positioning justice as a strategic theological resource for promoting moderate, adaptive, and humanistic religious practices in the context of modern diversity.